PERANCANGAN APLIKASI PENDATAAN PERPUSTAKAAN BERBASIS WEB DENGAN METHODE EXTREME PROGRAMMING DI SEKOLAH ADZKIA ISLAMIC SCHOOL - Zalsabilah, Rosdiana; Nurhasanah, Sri; Alfaridzi, Fernosha; Haryono, Wasis (Journal Information & Computer, 2023)
The density of existing internal and external school activities sometimes makes them forget to return books to the library, resulting in many books being held back. This condition causes losses for the borrower because they cannot borrow books that have not been returned. On the other hand, it also causes losses to the school because books that should be able to help in the learning process cannot be used. Another impact of the large number of books that have not been returned is that prospective borrowers must then regularly check whether the books are available or not. One of the causes of the above problems is the absence of a reminder of the borrowing time limit, causing many books to be returned late, and the unavailability of a communication platform between borrowers and librarian. From the description of the problem above, we need a web-based application that is able to provide return notifications, extend borrowing, and order books to be borrowed later.